Magnetism and granulometry of Pleistocene sediments of Dhapasi section, Kathmandu (Nepal): implications for depositional age and paleoenvironment - Gautam, Pitambar; Sakai, Tetsuya; Paudayal, Khum Narayan; Bhandari, Sudarshan; Gyawali, Babu Ram; Gautam, Chinta Mani; Rijal, Moti Lal (Bulletin of the Department of Geology, 2009)
A 28-m thick exposure of the younger stage deposits of Kathmandu Valley fluvio-deltaic deposits at Dhapasi has been studied for magnetic susceptibility (MS), remanent magnetization (RM), grain size characteristics of fine-grained sediments, and sedimentary fabric by anisotropy of magnetic susceptibility (AMS) . In situ volume MS (κ; in 10-3 SI) of the natural sediments ranges from 0.001 to 0.15, with lower range (45 to 34 Ka). Laser granulometry of fine-grained sediments from 76 levels reveals polymodal (2-4 modes) nature. With two prominent modes corresponding at 7.3 and 57.5 μm, these sediments plot into sandy silt, silt, and silty sand regions. MS correlates positively among broad grain size classes (i.e., increasing trend from sand through silt to clay). Mainly oblate susceptibility ellipsoids and low anisotropy degree shown by AMS data suggest a depositional fabric contributed by mainly paramagnetic minerals (e.g., phyllosilicates) responsible to low magnitudes of mass-specific MS (5-15 × 10-8 m3kg-1). Magnetic lineations or maximum susceptibility axes (kmax) are inferred to be predominantly NNW to SSE below ca. 18-m level, but NNE to SSW above. Such difference points to shift of paleoflow during the sediment deposition, and together with slight differences in grain-size parameters, in two prominent intervals of prodelta deposits, suggests significant changes in the paleodrainage configuration and source-sink relationship.   doi: 10.3126/bdg.v12i0.2247 Bulletin of the Department of Geology, Vol. 12, 2009, pp. 17-28